2011
DOI: 10.1517/13543784.2011.563236
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone as part of a prolonged release oxycodone/naloxone combination reduces oxycodone-induced slowing of gastrointestinal transit in healthy volunteers

Abstract: A single dose of oxycodone 20 mg significantly prolonged GI transit time but this effect was reduced by co-administration of naloxone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 17 publications
0
34
1
Order By: Relevance
“…11 For the PR naloxone period, our results are somewhat in contrast to a scintigraphic transit study by Smith et al, 22 who showed that a single dose of 10 mg PR naloxone in combination with 20 mg PR oxycodone significantly reduced colonic transit compared to PR oxycodone alone. The reason for this discrepancy between the studies remains obscure, but may reflect the different methodologies used to assess transit times.…”
Section: Gastrointestinal Transitcontrasting
confidence: 99%
See 1 more Smart Citation
“…11 For the PR naloxone period, our results are somewhat in contrast to a scintigraphic transit study by Smith et al, 22 who showed that a single dose of 10 mg PR naloxone in combination with 20 mg PR oxycodone significantly reduced colonic transit compared to PR oxycodone alone. The reason for this discrepancy between the studies remains obscure, but may reflect the different methodologies used to assess transit times.…”
Section: Gastrointestinal Transitcontrasting
confidence: 99%
“…The reason for this discrepancy between the studies remains obscure, but may reflect the different methodologies used to assess transit times. In our study, measurements rely on transport of a nondigestable solid, whereas Smith et al 22 used a radiolabelled resin to measure transit. Moreover, the dosage regimen and the drugs differed between the studies.…”
Section: Gastrointestinal Transitmentioning
confidence: 99%
“…The coadministration of OX and N optimal ratio in a fixed ratio of 2:1 did not significantly alter the bioavailability of either of its constituents [6]. A scintigraphic analysis showed that 20 mg of OX significantly increased colon arrival time and PR OXN 20/10 mg significantly reduced mean colonic transit time at values similar to placebo [7]. Two studies provided information about the optimal ratio of OX and N to obtain a significant improvement in bowel transit without influencing analgesia.…”
Section: Overview Of the Marketmentioning
confidence: 96%
“…Naloxone improved opioidinduced constipation symptoms and also reduced the laxative use with only mild opioid withdrawal symptoms such as yawning, sweating and shivering [Meissner et al 2000]. Naloxone PR reduced mean colonic transit time by 2.1 h when used in combination with oxycodone PR (20 mg oxycodone/10 mg naloxone) compared with oxycodone PR alone (20 mg) [Smith et al 2011]. …”
Section: Oxycodone and Naloxonementioning
confidence: 99%